Upaya Penanggulangan Hukum Pembunuhan Yang Dilakukan Anak Terhadap Keluarga - Alinar Ristika Gamis; Emilia Susanti; Nikmah Rosidah (Aliansi: Jurnal Hukum, Pendidikan dan Sosial Humaniora, 2024)
This research aims to analyze efforts to overcome the law of murder committed by children against their families. The type of research used is normative empirical. The data source was obtained from the field, namely LPKA Bandar Lampung. The results of the criminological analysis show that the crime of murder committed by children against their biological family is due to the presence of affection factors (Social Control Theory), anomie theory, differential association theory. The most dominant factor that causes the crime of murder committed by children is the factor of love for them from their families, especially their parents. Efforts to overcome murders committed by children against their biological families are through penal and non-penal means. The limitation of this research is that it only focuses on cases of child murder committed against their biological family and is not aimed at cases of murder against other people and the surrounding community. The contribution of this research at LPKA Bandar Lampung is to provide education regarding the applicable laws related to the murder of children against families.